2019
DOI: 10.1371/journal.pone.0211498
|View full text |Cite
|
Sign up to set email alerts
|

Poor supply chain management and stock-outs of point-of-care diagnostic tests in Upper East Region’s primary healthcare clinics, Ghana

Abstract: Introduction Several supply chain components are important to sustain point-of-care (POC) testing services in rural settings. To evaluate the availability of POC diagnostic tests in rural Ghana’s primary healthcare (PHC) clinics, we conducted an audit of the supply chain management for POC diagnostic services in rural Upper East Region’s (UER) PHC clinics, Ghana to determine the reasons/causes of POC tests deficiencies. Material and methods We conducted a review of acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…This revelation supports the findings of a previous study in Ghana which aimed to assess the accessibility of pregnancy-related POC diagnostic tests [18]. Similarly, a study aimed to audit the supply chain management of POC diagnostics in PHC clinics in Ghana also reported the stock-out of POC diagnostics [17]. The spatial pattern of the distribution of the health facilities providing HDP POC testing was revealed to be random.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This revelation supports the findings of a previous study in Ghana which aimed to assess the accessibility of pregnancy-related POC diagnostic tests [18]. Similarly, a study aimed to audit the supply chain management of POC diagnostics in PHC clinics in Ghana also reported the stock-out of POC diagnostics [17]. The spatial pattern of the distribution of the health facilities providing HDP POC testing was revealed to be random.…”
Section: Discussionsupporting
confidence: 84%
“…Despite this, previous studies in the Upper East Region (UER) of Ghana demonstrated low availability, weak supply chain management, and stock-outs of pregnancyrelated point-of-care (POC) tests including urine dipsticks for proteinuria and BP monitoring devices [16][17][18]. Previous research that evaluated geographical access to POC testing services focused on Tuberculosis [19], Glucose-6-Phosphate Dioxygenase Deficiency [20], and Blood Group and Rhesus Type [21].…”
Section: Introductionmentioning
confidence: 99%
“…Further, many primary care settings lack the necessary procurement linkages to ensure an ongoing supply of PPE and resources. [48][49][50] Without significant investment and support of mass production of PPE, and complementary supply chain support to ensure distribution, these shortages pose a serious threat to our ability to protect healthcare workers while safely providing comprehensive services to persons seeking care for COVID-19. There is a pressing need to provide guidance on supply chain management and operational continuity recommendations to ensure what UK NHS guidelines refer to as 'practice resilience' in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…This current study, therefore, mapped the geographical access to POC testing for G6PD deficiency as part of ANC services. The study setting has been adequately described in the earlier published cross-sectional survey and audit [29,30]. The 2019 project population of the region is approximately 1,273,677 (51.6% females) and is considered largely (79%) rural and scattered in dispersed settlements [33].…”
Section: Study Design and Settingmentioning
confidence: 99%
“…However, G6PD deficiency testing in Ghana is still a laboratory-based test (microscopy) and may not be accessible to all pregnant women particularly, those accessing ANC in rural primary healthcare (PHC) clinics. Although previous studies assessed the availability and supply chain management of point-of-care (POC) test including G6PD deficiency tests [29][30][31], geographical accessibility to comprehensive ANC POC testing [32], and evaluated a POC testing device for G6PD deficiency [5], to date, no study in Ghana has assessed the geographical accessibility to POC testing for G6PD deficiency. To inform national policy on G6PD deficiency screening test, support treatment decisions with anti-malarial medicines and SP administration to pregnant women in rural PHC clinics, the national malaria control or elimination program, and to improve equity to healthcare, we mapped the geographical access (distance and travel time) to POC testing for G6PD deficiency using geographical information systems.…”
Section: Introductionmentioning
confidence: 99%